Connecting Absences: Goodbye Ayacucho and the Performative Medium of Transmission - Robles-Moreno, Leticia (Latin American Theatre Review, 2011)
This essay analyzes Grupo Cultural Yuyachkani’s performance Goodbye Ayacucho and the multiple levels of mediatization found in the interplay between live performance and the online, archived video of the performance. From the actor’s body to the Internet users’ computers, each transmission entails an intersubjective relationality activated by a spectatorship’s embodied experience. Among the diverse ways in which new technologies and visual media are reshaping theatrical performance, the possibility of re-experiencing a performance through online videos provides a basis for reflection on the role that the spectator plays in the production of meaning during and after the performance. Online video performances are considered not only as a tool to make performances accessible to broader audiences, but also as a device that potentiates the most fundamental issues proposed by Yuyachkani and other theatrical collectives invested in the dialogue between performance and politics. Goodbye Ayacucho’s narrative, performance and online possibilities are an invitation to inhabit fragmentation, dispersion and multiplicity as modes of political resistance against colonizing claims of completeness and coherence. (LRM)